2008
DOI: 10.1038/ajh.2008.240
|View full text |Cite
|
Sign up to set email alerts
|

A Practice-Based Trial of Motivational Interviewing and Adherence in Hypertensive African Americans

Abstract: BACKGROUND Poor medication adherence is a significant problem in hypertensive African Americans. Although motivational interviewing (MINT) is effective for adoption and maintenance of health behaviors in patients with chronic diseases, its effect on medication adherence remains untested in this population. METHODS This randomized controlled trial tested the effect of a practice-based MINT counseling versus usual care (UC) on medication adherence and blood pressure (BP) in 190 hypertensive African Americans (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 39 publications
3
145
1
1
Order By: Relevance
“…Several other studies, 18,43,28 but not all, 44 have also shown that MINT is successful at improving medication adherence. The current study extends this literature by showing that a phone-based approach is effective among a large, geographically dispersed sample of minority patients whom had recently undergone a major cardiovascular procedure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several other studies, 18,43,28 but not all, 44 have also shown that MINT is successful at improving medication adherence. The current study extends this literature by showing that a phone-based approach is effective among a large, geographically dispersed sample of minority patients whom had recently undergone a major cardiovascular procedure.…”
Section: Discussionmentioning
confidence: 91%
“…MINT delivered in person has been successful at reducing weight; achieving smoking cessation; improving cardiovascular risk profile; [24][25][26][27] and improving adherence, particularly to HIV medications. 18,[28][29][30] For the study, we trained two Humana nurses in the delivery of MINT. Training consisted of a 3-day workshop conducted by an experienced MINT trainer and by a specialist in the MINT Integrity Coding system (MITI).…”
Section: Interventionsmentioning
confidence: 99%
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…Behavioral interventions often require multiple contacts with patients to optimize their effectiveness. 32 The positive impact on secondary outcomes and the dose response of PMA contact with PACT staff and patients on BP control suggest that a longer intervention may result in improvements in the primary clinical outcomes of hypertension control and smoking cessation. With 78 % of hypertensive patients having controlled BP at baseline, this Bceiling^effect may have limited the impact of the intervention.…”
Section: Discussionmentioning
confidence: 99%